Impact of Sound Decision-Making on Small and Medium Businesses in Pakistan - Adnan Ullah; Sajid Dawood Khan (International Journal of Asian Business and Management, 2024)
This research aims to investigate the significance of sound decision-making in the success and sustainability of Small and Medium Businesses (SMBs). The study will concentrate on key constructs such as risk management, financial stability, innovation and adoption, and customer relationship management. The study uses a quantitative approach, surveying a sample of SMB owners and managers in Pakistan's different industries to gather data. In order to find out how respondents feel about decision-making processes and how they affect SMB performance, a structured questionnaire is used. Regression analysis is one of the statistical techniques used to examine the data and evaluate the hypotheses. The results demonstrate how important sound decision-making is to the resilience and success of SMBs in Pakistan. Financial stability stands out as a crucial component that impacts the performance of small and medium-sized businesses (SMBs). This is followed by efficient risk management, innovation and adoption, and customer relationship management. These results highlight how crucial strategic decision-making is for promoting SMB sustainability and growth in a fast-paced business climate. The results provide useful information to managers, owners, and regulators of SMBs who want to improve SMB decision-making procedures. Small and medium-sized businesses (SMBs) can enhance their competitive standing, boost operational effectiveness, and promote long-term growth and profitability by placing a high priority on financial stability, proactive risk management, innovation, and customer-centric methods